Evolutions of Labor Tax at The Eu 27 Level, Comparisons, Romania In Relation to The Eu 27 - Florina POPA (Communications of International Proceedings, 2024)
This paper aims to analyze the evolution over a period of thirteen years (2009-2021) , of  Labour Tax Revenues, expressed as a share in GDP (% of GDP), both  at EU-27  level  and for Romania in relation to the countries of the European Union (in terms of percentage values and hierarchical position). The motive behind the study lies in the importance of studying the evolution of Labour Tax Revenues, both for European Union - EU27  and for Romania, over a period of thirteen years (2009-2021): to know the position of different Member Countries with lower or higher level of Labour Tax Rate compared to EU-27 average; the evolution of revenue from Labour Tax in Romania in relation to EU 27,  its hierarchical position towards the EU-27 countries. The study containing data analysis, graphs and tables (represented on the basis of European Union data) resulting from the evolution of  Labour Tax Revenue, expressed as a share in GDP, both for the European Union - EU27 and for Romania, on the interval 2009-2021, it was desired to be original towards the frequent analyzes encountered in the specialized papers. The methodology used in the study was the research from specilezed literature, processing of ideas through the author's own interpretation, the collection of statistical database, analysis of the announced elements, representation in graphs and tables, in order to highlight the results obtained. Summary of the findings reflects the synthesis of ideas resulted from data analyzed concerning the evolution of Labour Tax Revenues, expressed as a share in GDP, at EU-27 level and of  Romania in relation to the countries of the European Union, for the period 2009-2021.
Keywords: labour tax; revenues; evolutions; comparisons; hierachy; EU 27; Romania.